Pectoral Nerve Blocks for Breast Augmentation Surgery: A Randomized, Double-blind, Dual-centered Controlled Trial. (28th June 2021) - Aarab, Yassir; Ramin, Severin; Odonnat, Thomas; Garnier, Océane; Boissin, Audrey; Molinari, Nicolas; Marin, Grégory; Perrigault, Pierre-Francois; Cuvillon, Philippe; Chanques, Gérald
Abstract : Background: Pectoral nerve blocks have been proposed for analgesia during and after breast cancer surgery, but data are conflicted in aesthetic breast surgery. This trial tested the primary hypothesis that adding a preincisional pectoral nerve block is superior to systemic multimodal analgesic regimen alone for pain control after breast augmentation surgery. A second hypothesis is that rescue opioid consumption would be decreased with a long-lasting effect for both outcomes during the following days. Methods: Seventy-three adult female patients undergoing aesthetic breast augmentation surgery under general anesthesia were randomly allocated to receive a pectoral nerve block versus no block. Both groups received standard care with protocolized multimodal analgesia alone including systematic acetaminophen and nonsteroidal anti-inflammatory drugs. The primary outcome measure was the maximal numerical rating scale in the first 6 h after extubation. Secondary outcomes included intraoperative remifentanil consumption and from extubation to day 5: maximal numerical rating scale, postoperative cumulative opioid consumption and postoperative opioid side effects, and patient satisfaction recorded at day 5. Results: The maximal numerical rating scale score in the first 6 h was lower in the pectoral nerve block group compared with the control group (3.9 ± 2.5 vs. 5.2 ± 2.2; difference: –1.2 [95% CI, –2.3 to –0.1]; P = 0.036). The pectoral nerve block group had a lower maximal numerical rating scale between days 1 and 5 (2.2 ± 1.9 vs. 3.2 ± 1.7; P = 0.032). The cumulative amount of overall opioids consumption (oral morphine equivalent) was lower for the pectoral nerve block group from hour 6 to day 1 (0.0 [0.0 to 21.0] vs. 21.0 [0.0 to 31.5] mg, P = 0.006) and from days 1 to 5 (0.0 [0.0 to 21.0] vs. 21.0 [0.0 to 51] mg, P = 0.002). Conclusions: Pectoral nerve block in conjunction with multimodal analgesia provides effective perioperative pain relief after aesthetic breast surgery and is associated with reduced opioid consumption over the first 5 postoperative days. Abstract : Patients undergoing breast augmentation who received pectoral nerve blocks in addition to multimodal analgesia experienced less pain in the first 6 h postoperatively and lower maximal pain scores between postoperative days 1 and 5. The use of pectoral nerve blocks also reduced opioid consumption up to 5 days after surgery.